Mother-to-child transmission of HIV: risk factors and missed opportunities for prevention among pregnant women attending health services in Goiânia, Goiás State, Brazil Transmissão vertical do HIV: fatores associados e perdas de oportunidades de intervenção em gestantes atendidas em Goiânia, Goiás, Brasil - Marília Dalva Turchi; Lucélia da Silva Duarte; Celina Maria Turchi Martelli (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2007)
The objectives of this study were to estimate the risk of vertical HIV transmission and assess the associated factors and missed opportunities for prevention in a cohort of HIV+ pregnant women (1995-2001) treated in Goiânia, Goiás, Brazil, with follow-up of their children until 2005. Three data sources were compared: Information System on Reportable Diseases (SINAN), Information System on HIV+ Pregnant Women and Exposed Children (SISGHIV), and patient clinical charts. The study estimated the vertical transmission rates, factors associated with vertical transmission, and use of antiretroviral therapy. 276 HIV+ women were identified (322 pregnancies), and there were 70 HIV+ children. Overall risk of vertical HIV transmission was 27.8%. The vertical transmission rate was 40.8% in the group without prophylaxis and 1% in the group with adequate prophylaxis, i.e., a 97.5% reduction in transmission risk. Year of delivery, consultation with a specialist, and no history of injecting drug use were factors associated with adequate use of antiretroviral therapy. The study showed an important reduction in the risk of vertical transmission in pregnant women who received adequate therapy, besides identifying missed opportunities for prevention. Os objetivos foram estimar o risco de transmissão vertical do HIV e avaliar fatores associados e perdas de oportunidades de prevenção em coorte de gestantes HIV+ (1995-2001), atendidas em Goiânia, Goiás, Brasil, com seguimento das crianças até 2005. Foi realizada conciliação de três fontes de dados: Sistema de Informação de Agravos de Notificação (SINAN), Sistema de Informação de Gestantes HIV Positivas e Crianças Expostas (SISGHIV) e prontuários médicos. Foram estimados os percentuais de transmissão vertical, fatores associados à transmissão vertical e ao uso de terapia anti-retroviral. Foram identificadas 276 mulheres HIV+ (322 gestações) e os desfechos foram 70 crianças HIV+. O risco de transmissão vertical do HIV foi de 27,8%. A transmissão vertical foi de 40,8% no grupo sem profilaxia e de 1% no grupo com profilaxia adequada, com 97,5% de redução do risco de transmissão. Ano do parto, consulta com especialista e não ter antecedentes de drogas injetáveis foram fatores associados ao uso adequado de terapia anti-retroviral. O estudo evidenciou importante redução do risco de transmissão vertical em gestantes que receberam terapia adequada e identificou oportunidades perdidas para prevenção.